2011
DOI: 10.4067/s0717-95022011000200037
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Proliferating Cell Nuclear Antigen (PCNA) in Dental Follicles of Impacted Third Molars

Abstract: SUMMARY:This study investigated the immunodetection of PCNA in epithelial components of dental follicles associated with impacted third molars without radiographical and morphological signs of pathosis. A total of 105 specimens of dental follicles associated with impacted third molars with incomplete rhizogenesis (between Nolla's stage 6 and 9) were surgically removed from 56 patients. Epithelial cell proliferating was determined by using immunohistochemical labeling. Statistical analysis was performed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…The proliferative potential of dental follicles surrounding the crown of unerupted/impacted teeth has not yet been investigated in detail. Earlier studies focused on the follicles of impacted mandibular third molars (Szelachowska et al;Piattelli et al;Adelsperger et al, 2000;da Silva Baumgart et al, 2007;Oliveira et al, 2011Oliveira et al, , 2012Özarslan et al, 2013) and their associated pathologies (Saraçoglu et al, 2005;Edamatsu et al, 2005;Cabbar et al, 2008;Güler et al, 2012). To the knowledge of the authors, there is no data on the proliferative capacity of follicles of impacted teeth other than mandibular third molars.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…The proliferative potential of dental follicles surrounding the crown of unerupted/impacted teeth has not yet been investigated in detail. Earlier studies focused on the follicles of impacted mandibular third molars (Szelachowska et al;Piattelli et al;Adelsperger et al, 2000;da Silva Baumgart et al, 2007;Oliveira et al, 2011Oliveira et al, , 2012Özarslan et al, 2013) and their associated pathologies (Saraçoglu et al, 2005;Edamatsu et al, 2005;Cabbar et al, 2008;Güler et al, 2012). To the knowledge of the authors, there is no data on the proliferative capacity of follicles of impacted teeth other than mandibular third molars.…”
Section: Introductionmentioning
confidence: 79%
“…We were unable to statistically compare the metabolic activity of the single strand reduced enamel epithelium and the stratified variant as we had only two specimens with reduced enamel epithelium. Adelsperger et al, found that 5 of 8 specimens with squamous metaplasia demonstrated PCNA uptake, whereas none of 10 specimens with no squamous metaplasia were PCNA positive while de Oliveira et al (2011) demonstrated positivity for proliferating cell nuclear antigen (PCNA) in 3 out of 15 dental follicles with stratified squamous lining epithelium. The authors concluded that cellular proliferative activity might be active in dental follicles showing squamous metaplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the justification for prophylactic removal of ILTMs is less certain and has been debated for many years. [5] Odontogenic cysts or odontogenic tumors may arise from the epithelial rests in the follicle tissue surrounding impacted tooth. The potential for this development is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial lining of the specimens were classified according to the type (absent, enamel reduced and stratified squamous) and cell activity (hyperplastic and inactive). The remaining epithelium in the connective tissue was classified as inactive or proliferative when present (de Oliveira et al, 2011).…”
Section: Methodsmentioning
confidence: 99%